2007
DOI: 10.1111/j.1582-4934.2007.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in cancer stem/progenitor cell research: therapeutic implications for overcoming resistance to the most aggressive cancers

Abstract: Overcoming intrinsic and acquired resistance of cancer stem/progenitor cells to current clinical treatments represents a major challenge in treating and curing the most aggressive and metastatic cancers. This review summarizes recent advances in our understanding of the cellular origin and molecular mechanisms at the basis of cancer initiation and progression as well as the heterogeneity of cancers arising from the malignant transformation of adult stem/progenitor cells. We describe the critical functions prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
238
0
14

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(255 citation statements)
references
References 238 publications
(863 reference statements)
3
238
0
14
Order By: Relevance
“…The mechanisms by which integrins are regulated need to be characterized by focusing on modulators of integrin expression. Yet another promising avenue of research is to elucidate the role of integrins in promoting proliferation of prostate cancer stem cells, in particular, a 2 b 1 appears to be interesting since it is highly expressed in these cells (Collins et al 2005, Mimeault et al 2007. Finally, an under-investigated area in prostate cancer research is the cross talk between bone microenvironment and metastasis (Mohla 2004), to which the interactions between integrins and their ECM ligands are likely to contribute significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms by which integrins are regulated need to be characterized by focusing on modulators of integrin expression. Yet another promising avenue of research is to elucidate the role of integrins in promoting proliferation of prostate cancer stem cells, in particular, a 2 b 1 appears to be interesting since it is highly expressed in these cells (Collins et al 2005, Mimeault et al 2007. Finally, an under-investigated area in prostate cancer research is the cross talk between bone microenvironment and metastasis (Mohla 2004), to which the interactions between integrins and their ECM ligands are likely to contribute significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [4] demonstrated that CD44+CD117+ cells are ovarian cancer-initiating cells. CD133 is also a surface marker for CSCs, including those in the brain, prostate, pancreas, liver, colon, and skin cancers [30,31] . Some recent studies indicated that CD133 expression defined a tumor-initiating cell population in human ovarian cancer [8,32] .…”
Section: Discussionmentioning
confidence: 99%
“…OCSCs are characterized by 11111111111  their capacity to survive and organize suspended spheroid structures in serum-free medium, overexpression of several stem cell markers (ABCG2, Nanog, Nestin, and Oct4) [4,10] , CD44+, CD117+, CD133+, as well as resistance to conventional chemotherapies, resistance to apoptosis, and the ability to recapitulate the original tumor in vivo [4,[6][7][8]11] .…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report the safety and immunogenicity of an apoptotic B16F10 tumor cell vaccine in a controlled study of C57BL/6 mice. 5 wild-type B16F10 cells as control. In the antitumor effect experiment, C57BL/6 mice were randomly divided into the experimental, the B16F10 cell and the PBS control groups.…”
Section: Introductionmentioning
confidence: 99%
“…In the antitumor effect experiment, C57BL/6 mice were randomly divided into the experimental, the B16F10 cell and the PBS control groups. Each mouse was immunized s.c. in the abdominal region, respectively, with a vaccine of 5x10 5 B16F10 tumor cells treated with MIT in combination with RP and VP for 12 h or 1x10 5 wild-type B16F10 cells inactivated with mitomycin C or 100 µl PBS. The same immunization was repeated twice at an interval of 2 weeks.…”
Section: Introductionmentioning
confidence: 99%